The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s11655-014-2026-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of Chinese medicine with allogeneic hematopoietic stem cell transplantation for severe aplastic anemia patients

Abstract: Treatment with the KBS formulation may reduce the rate of graft failure and treatment-related mortality and improve the rate of OS in SAA patients with allo-HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A study on autologous and allogenic HSC transplanted in patients with chronic granulocytic leukaemia, acute non-lymphocytic leukaemia and lymphoma were treated with CHM concluded that treating with CHM reduces complications of transplantations and promotes recovery of haematopoietic functions [36]. More research on various other HSC transplantations against haematological malignancies such as severe aplastic anaemia patients [37], patients with myelodysplastic syndrome [38] and acute paediatric leukaemia [39] were cited herein [35], which had given positive results on patient survival rates, reduction of complications and increasing functional properties of haematopoietic cells. However, most of these studies were based on a low number of samples; hence, the need to perform such studies in large populations arises in order to validate and standardize the CHM procedures.…”
Section: Effects Of Herbal Extracts On Human Stem Cells 21 Stimulatmentioning
confidence: 99%
“…A study on autologous and allogenic HSC transplanted in patients with chronic granulocytic leukaemia, acute non-lymphocytic leukaemia and lymphoma were treated with CHM concluded that treating with CHM reduces complications of transplantations and promotes recovery of haematopoietic functions [36]. More research on various other HSC transplantations against haematological malignancies such as severe aplastic anaemia patients [37], patients with myelodysplastic syndrome [38] and acute paediatric leukaemia [39] were cited herein [35], which had given positive results on patient survival rates, reduction of complications and increasing functional properties of haematopoietic cells. However, most of these studies were based on a low number of samples; hence, the need to perform such studies in large populations arises in order to validate and standardize the CHM procedures.…”
Section: Effects Of Herbal Extracts On Human Stem Cells 21 Stimulatmentioning
confidence: 99%
“…The name “aplastic anemia” does not appear in the ancient Chinese classics, whose clinical manifestations tend to be “consumptive disease” or “hemorrhagic syndrome” in traditional Chinese concepts [ 18 ]. In the 1950s, AA was thought to be a deficiency of Qi and blood according to the clinical manifestations of the patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported it could improve adhesion molecules expression levels of bone marrow mesenchymal stem cells (BMSCs) in AA patients [ 8 , 9 ]. Besides treatment with the kidney-reinforcing, blood-activating, and stasis-removing herbals could reduce the rate of graft failure and treatment-related mortality and improve the rate of overall survival (OS) in severe AA patients with allogeneic hematopoietic stem cell transplantation (allo-HSCT) [ 10 ]. However, its underlying mechanism for AA treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%